The Importance of Insurance in Reducing Systematic Risk and Aiding Poverty Alleviation: A Review of Financial Protection - Aisyah Abdul Jabbar; Edwards Geraldine; M Muthoifin; Ishmah Afiyah (Solo International Collaboration and Publication of Social Sciences and Humanities, 2024)
This study aims to investigate the important role of insurance in reducing systematic risk and helping poverty alleviation through a review of financial protection. This study uses a descriptive-analytical approach by analyzing various related literature covering theories and practices related to insurance, systematic risk, and poverty alleviation. Data was collected through literature studies involving scientific journals, reference books, and recent research reports. The results showed that insurance plays a crucial role in reducing systematic risk by providing a mechanism for risk transfer from affected individuals or groups to insurance institutions. Thus, insurance helps protect individuals and families from unexpected events such as natural disasters, accidents, or illnesses that can lead to poverty. In addition, insurance also plays a role in poverty alleviation by providing important financial protection for those who are vulnerable to adverse financial risks. Therefore, understanding and access to adequate insurance is essential in efforts to reduce systematic risks and improve the overall welfare of society. This research provides a theoretical and practical foundation for relevant parties, including governments, financial institutions, and the general public, to improve the understanding and application of insurance as an important instrument in reducing systematic risks and alleviating poverty through effective financial protection